A Rare Benign Pancreatic Lesion Mimicking Malignancy- Eosinophilic Pancreatitis - Kurşat Rahmi Serin; Muharrem Oner; Nadir Adnan Hacım; Ali Emre (Archives of Clinical Gastroenterology - Peertechz Publications, 2018)
Background: Eosinophilic infiltration of the pancreas is usually associated with generalized diseases like "sclerosing pancreatitis", "eosinophylic gastroenteritis" and "systemic mastocytosis". Most patients have systemic findings such as eosinophilia, elevated IgE levels and gastrointestinal tract infiltration Isolated eosinophilic infiltration of the pancreas is much less common and is usually found in the histological evaluation of pancreatic specimens resected with the misdiagnosis of pancreatic cancer.  Methods: Herein we report a rare benign pancreatic tumor that was operated on with the misdiagnosis of malignancy.  Results: A 47-year-old woman underwent laparotomy with the diagnosis of cholestasis and suspected stone image in the common bile duct. No stone was found in the biliary tract; however, a pancreatic head mass was discovered. It was considered unresectable. Cholecystectomy and T-tube drainage was performed. The operative biopsy was non-diagnostic and the patient was referred to our clinic. Radiologic findings revealed a resectable pancreatic head mass. A standard pancreatoduodenectomy was performed. The postoperative period was uneventful. Tissue diagnosis was "eosinophilic pancreatitis", without stomach, duodenum, and proximal jejunum involvement. No inflammation was detected on postoperative colonoscopy.  Conclusion: Rare inflammatory pancreatic diseases such as eosinophilic pancreatitis mimics malignancy. If a definitive diagnosis can be achieved before operative decision, the disease can be treated nonsurgically.